Secukinumab-Induced Inflammatory Bowel Disease in a Patient Treated for Chronic Plaque Psoriasis and Psoriatic Arthritis: A Case Report and Review of the Role of Novel Biologic Agents Targeting the p19 Subunit of IL-23 - K. M. Darch; T. L. Holland; L. J. Spelman (Case Reports in Medicine)
Chronic plaque psoriasis and psoriatic arthritis are common autoimmune inflammatory conditions, often existing as comorbidities that have a significant impact on a patient’s quality of life. The availability of a range of novel, targeted therapies for their treatment, most notably the availability of biologic agents, has revolutionised management of these conditions and allowed for significant improvements in patient outcomes. Secukinumab (Cosentyx), a fully-human monoclonal antibody that acts by selectively binding to and neutralising the proinflammatory cytokine IL-17A, is used widely for the treatment of both chronic plaque psoriasis and psoriatic arthritis. In this report, we discuss the case of a 54-year-old female with chronic plaque psoriasis and psoriatic arthritis, who experienced the onset of symptoms and was subsequently diagnosed with Crohn’s disease during treatment with secukinumab. It was determined by the gastroenterologist that this may represent secukinumab-induced inflammatory bowel disease. We will review the current understanding of the role of IL-17 in inflammatory bowel disease and the important role of novel agents that target the p19 subunit of IL-23 which have shown significant promise in the management of not only chronic plaque psoriasis and psoriatic arthritis, but also inflammatory bowel disease itself.